Deposição e caracterização de filmes finos de BiFeO3 - Ávila, Renan Moreira Costa (2017)
In modern times, apparently, there is nothing more to be discovered, and comes the need to constantly improve what already exists, as in the case of electronic devices such as memories, sensors and many others. Therefore, materials presenting multiple physical properties and/or states, such as multiferroic, has gained much attention in academic and industrial environments due to the possibility of devices miniaturization and increased efficiency compared to those already on the market. Among these materials are bismuth ferrite (BiFeO3) , which have ferroelectric properties at room temperature. Bismuth ferrite also presents, under certain conditions, mensurable antiferromagnetic properties. But there are still open questions, especially on Bismuth ferrite. Examples are the frequent formation of secondary spurious phases during deposition, high density of leakage current, and the cycloid ordering of spins in the bulk material that inhibits the simultaneous observation of antiferromagnetism and ferroelectricity. Some authors have reported that cycloid ordering in BiFeO3 can be suppressed in high quality epitaxial thin films. So in this work we aim to deposit BiFeO3 thin films by Pulsed Electron Deposition (PED) and characterize them by X-ray diffraction (XRD) and Fourier transform infrared spectrometry (FTIR) in order to better understand the deposition process, analyze the chemical and structural properties of the deposited films and, if possible, improve the quality of these films. As the main result, conditions were found in which BiFeO3 epitaxial thin films can be obtained by PED technique.